Factors influencing the intention to re-use e-learning among students of Malaysian universities with e-learning facilities - Siva Prakash, Ramasamy (2021)
E-learning is regarded as a mandatory teaching and learning approach in higher education worldwide. The effectiveness of e-learning depends on the successful adoption by the student. E-learning is considered the most appropriate effective method of knowledge delivery to meet the current academic requirements. Hence, this study was essential to examine the factors affecting the intention to use e-learning among students in Malaysian higher education institutes. Based on the technology acceptance model (TAM) and the theory of planned behaviour (TPB) this study developed a comprehensive framework on students' intention to use e-learning. A quantitative research method that suited the research objective was adopted. This study used the random sampling technique, data was collected from 330 respondents who were enrolled in public and private universities with e-learning facilities in Malaysia. The result showed that Attitude, Perceived usefulness, and Perceived behavioural becomes a positive predictor of Intention to use e-learning. However, Subjective norms found no significant effect on Intention to use e-learning. The results revealed that all the constructed hypotheses were supported except for H3, which reported that the subjective norm did not have a significant positive influence on the intention to use e-learning. The obtained results have significant contributions to theory and practice in e-learning delivery. The findings of the study provide clear insight to researchers and practitioners on the usage of e-learning among distance-learning students as well as the variations in the intention to use e-learning between male and female learners. Besides, as a practical contribution, this study suggests that university managements should improve their e-learning facilities to benefit their stakeholders, especially the students.